2020
DOI: 10.4103/jcd.jcd_371_19
|View full text |Cite
|
Sign up to set email alerts
|

Sealing ability of three different root repair materials for furcation perforation repair: An in vitro study

Abstract: Aim: The present study aimed to evaluate and compare the sealing ability of mineral trioxide aggregate (MTA)-Angelus, Biodentine™, and EndoSequence cement in furcation perforations using protein leakage assessment. Materials and Methods: The present study was conducted using seventy extracted human maxillary and mandibular molars with intact furcation. The samples were randomly allocated into three groups ( n = 20) based on repair material use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A limitation of the current study is that the use of an in vitro model may not completely recapitulate the exact clinical situation. Several recent studies from 2019-2021 [52][53][54] attempted to compare the sealing ability of different bioceramic materials, but these used dye extraction [52,53] or protein leakage [54] models without any added bacterial contamination. Further in vivo studies will be needed to assess the antibacterial activity of various calcium silicate-based materials in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the current study is that the use of an in vitro model may not completely recapitulate the exact clinical situation. Several recent studies from 2019-2021 [52][53][54] attempted to compare the sealing ability of different bioceramic materials, but these used dye extraction [52,53] or protein leakage [54] models without any added bacterial contamination. Further in vivo studies will be needed to assess the antibacterial activity of various calcium silicate-based materials in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sealing ability of the repairing material is a critical factor for the purpose of blockage of continuing contamination. The sealing ability and handling properties of Biodentine and EndoSequence were superior to MTA Angelus for repairing perforation of furcations [ 125 ]. Interestingly, Solanki et al summed up their systematic review study that its favorable biological properties along with its good sealing ability make Biodentine a competent retrograde filling material for clinical use [ 126 ].…”
Section: Clinical Applications Of Calcium Silicate Cementsmentioning
confidence: 99%
“…Kakani et al [ 260 ] compared the sealing quality of MTA, Biodentine, and EndoSequence cements in perforations, and observed minimum, intermediate, and maximum leakage of Biodentine, EndoSequence, and MTA, respectively. The authors suggested that both Biodentine and Endosequence may be used as replacements for MTA during the repair of perforations.…”
Section: Biomimetic Materials In Endodonticsmentioning
confidence: 99%